2019
DOI: 10.2147/ott.s189471
|View full text |Cite
|
Sign up to set email alerts
|

<p>LINC00565 promotes proliferation and inhibits apoptosis of gastric cancer by targeting miR-665/AKT3 axis</p>

Abstract: BackgroundNumerous studies have shown that long noncoding RNA (lncRNA) is involved in gastric cancer (GC). A relevant microarray containing gastric cancer-related lncRNAs was downloaded from The Cancer Genome Atlas database.MethodsqRT-PCR was used to analyze LINC00565 and AKT3 expression in tumor tissues and cell lines. Proliferative, colony formation and apoptotic abilities of GC cells after transfection of sh-LINC00565 were determined by CCK-8, colony formation assay and flow cytometry, respectively. RIP was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…19 LINC00565 is a tumorassociated lncRNA involved in the development of ovarian cancer and gastric cancer. 17,18 We collected 52 paired EC tissues and paracancerous tissues and detected the relative levels of LINC00565 and KLF9 in EC tissues. LINC00565 was up-regulated and KLF9 was down-regulated in EC tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 LINC00565 is a tumorassociated lncRNA involved in the development of ovarian cancer and gastric cancer. 17,18 We collected 52 paired EC tissues and paracancerous tissues and detected the relative levels of LINC00565 and KLF9 in EC tissues. LINC00565 was up-regulated and KLF9 was down-regulated in EC tissues.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16] It is previously reported that LINC00565 is an oncogene triggering deterioration of tumor development. 17,18 However, its potential role in EC remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…To comprehensively characterize those aberrantly expressed lncRNAs, we analyzed CRC and normal tissue RNA sequencing data downloaded from The Cancer Genome Atlas (TCGA). In order to identify CRC-associated lncRNAs, the literature was searched to identify a novel lncRNA named LINC00565 has already been discovered in gastric cancer ( 13 ). LINC00565 spans 2,478 bp length and is located on chromosome 13, which is significantly upregulated in gastric cancer (GC) tissues ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…In order to identify CRC-associated lncRNAs, the literature was searched to identify a novel lncRNA named LINC00565 has already been discovered in gastric cancer ( 13 ). LINC00565 spans 2,478 bp length and is located on chromosome 13, which is significantly upregulated in gastric cancer (GC) tissues ( 13 ). LINC00565 drives the progression of ovarian cancer by targeting GAS6 ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation